ANTHROPOMETRIC AND PHYSICAL CHANGES IN COMMUNITY DWELLING OLD ADULTS DURING A 12 WEEK RESISTANCE EXERCISE PROGRAM. (11th November 2018) - Geirsdottir, O; Chang Gudjonsson, M; Jonsson, P; Thorsdottir, I; Ramel, A
Abstract: Resistance exercise is important for the prevention of sarcopenia and physical dependence of old adults. However, little is known whether overweight/obesity affect the outcomes of a resistance exercise program. Community dwelling Icelandic old adults (N=236, 73.7 ± 5.7 years) participated in a 12-week resistance exercise program. Anthropometrics, muscular strength and physical function were measured at baseline and endpoint. Participants were grouped retrospectively into normal-, overweight and obese according to BMI. Statistical analyses were corrected for age and gender. Of the participants, 22.0% were normal-, 41.4% were overweight and 36.6% were obese. All groups experienced improvements in outcome measurements, but improvements in obese individuals were less pronounced compared to normal weight individuals. Normal weight individuals gained more lean mass (+0.70kg, P=0.015), appendicular muscle mass (+0.42kg, P=0.007) but tended to loose more fat mass (-0.75kg, P=0.081) as compared to obese. Absolute gains in quadriceps strength were similar between groups, but relative to body weight, normal weight subject gained more than obese subjects (+0.31N/kg, P=0.017). This translated into an greater improvement in 6-minutes-walk-for-distance (+24. m, P< 0.001) compared to obese subjects. Interestingly, grip strength increased more in obese subjects (2.4 lb., P=0.020). Timed-up-and-go improved similarly in all groups (-0, 64sec, P< 0.001). Independently from their body weight status, old adults benefited from a resistance exercise program in terms of body composition and physical function. However, obese individuals improved significantly less than normal weight participants although there was similar attendance to the exercise classes. Great care has to be taken of obese elderly in order to maintain their physical independence as long as possible.